Cloud Data Integration Tools As Services - Nisreen Nizar Raouf; Mohammad A. Taha Aldabbagh (Jurnal Kendali Teknik dan Sains, 2024)
In this paper, a variety of data integration, cloud computing, and web services-related topics were discussed. The conversation covered the advantages of using cloud-based methods for cloud-based data integration, such as enhanced data accuracy and completeness, as well as the challenges and considerations that must be addressed. In addition, the significance of document integrity and the use of auto-enhance document tools to ensure data accuracy were emphasized. The paper also provided a broad overview of the subject, touching on a variety of aspects and providing insights into the potential of cloud-based data integration methods in the cloud industry.